Pengaruh Lingkungan Kerja dan Job Insecurity Terhadap Motivasi Kerja dan Dampaknya pada Kinerja Karyawan Outsourcing Mall Lippo Cikarang - Lim Sanny; Selby Kristanti (Binus Business Review, 2012)
Mal Lippo Cikarang a shopping center that uses outsourcing employees to manager level down. The purpose of this study is to analyze the influence of work environment and job insecurity on work motivation and its impact on employee performance Outsourcing in Lippo Cikarang Mall. The method of analysis used in this study are Pearson correlation and path analysis. Data obtained from the assessment of employees through questionnaires and interviews. Results achieved in this study was to determine that the work environment at the Mall Lippo Cikarang less convenient and there is job insecurity on the company and therefore contributes less well on work motivation and employee performance Outsourcing in Lippo Cikarang Mall. Job insecurity has a weak and a significant effect on work motivation and employee performance and work environment has a fairly strong relationship and significant impact on employee motivation and performance. Motivation to work has a strong relationship to the employee's performance. With the company is expected to focus on increasing motivation and improving the working environment at the Mall Lippo Cikarang and member attention on job insecurity. In addition, the expected results of this research can provide input to the Mall Lippo Cikarang so as to improve employee performance Outsourcing as well.